Effects of Cu addition on the corrosion behavior of NiCoCrMo alloys in neutral chloride solution. Issue 65 (22nd August 2017) - Yang, Biaobiao; Li, Jiaxiang; Gong, Xiaojuan; Nie, Yan; Li, Yunping
Abstract : The influence of Cu addition (0–4 mass%) on the corrosion behavior of Ni–30Co–16Cr–15Mo alloy in neutral chloride solution is investigated by electrochemical measurements. Some essential surface analysis are also conducted to explain the corrosion mechanism. Abstract : The influence of Cu addition (0–4 mass%) on the corrosion behavior of Ni–30Co–16Cr–15Mo alloy in neutral chloride solution is investigated by electrochemical measurements. The results indicate that alloy with 0.5 mass% Cu shows inferior corrosion resistance compared to Cu-free alloy under open-circuit potential, which is possibly ascribed to the galvanic corrosion from the insufficient coverage of Cu on the passive film; a higher fraction of Cu results in a significant improvement on corrosion resistance, and Cu is believed capable of strengthening the passivation and postponing the oxidization of dominant Cr(iii ) in the passive film into more soluble Cr(vi ).